Changes in the characteristics of Spanish poor households: the case of Imputed Rent - Jose Calvo; Cristina Sánchez (European Regional Science Association (ERSA), 2010)
Poverty has been an important area of study in Spain for a long period of time. Many authors have analyzed the number and characteristics of Spanish poor population. Nevertheless, one of the most important criticisms to Spanish studies is related to the variable selected to proxy household's income. Until 2007 the Survey on Income and Living Conditions (SILC) did not include an estimation of the value of house's ownership. The lack of that estimation could provoke biased results at least by two ways: it underestimates some incomes and, at the same time, it affects families' distribution around the poverty line. In 2007 this variable, called Imputed Rent (IMRENT), was calculated for the first time in Spain. Therefore, it was possible to use it and compare the results obtained following the traditional methodology or introducing a new calculation of Income per Unit of Equivalent Consumption in Spanish households taking into account IMRENT. We present a descriptive analysis and a probit estimation to calculate the probability of leaving poverty when the variable is considered. The results show the relevance of this proxy to households' wealth since its incorporation change the profile of Spanish poor: if we do not consider it most people older than 65 years are under poverty line, especially women. But if we include it a big share of widows and retired people cross the border and leave poverty. There is a clear economic policy implication: in the actual situation, with problems to finance Public Pensions' System, it should be necessary to take into account not only current income but wealth to calculate Spanish widow's and retirement pensions. We also obtain a positive effect of been the house owners or if the family is paying a mortgage.
Keywords: 330